'Natural leaders of a democratic army': Parliament goes to war 'Les dirigeants naturels d'une armée démocratique': Le Parlement s'en va t'en guerre. Issue 1 (March 2017) - Barrett, Matthew
Abstract : During the First World War, 25 Canadian members of the federal Parliament and provincial legislatures recruited infantry battalions from their constituencies. Perceiving themselves to be Canada's 'natural leaders', middle-aged parliamentary colonels believed prominence and success in public life exemplified the qualities of moral leadership and strong character necessary for military command. After landing in England, however, the vast majority of the units were broken up and most of the former commanders were denied front-line positions due to age and unfitness. This article details how the colonels coped with the loss of their battalions, which undermined their self-image as natural military leaders and challenged their masculine authority. Defending their reputations against accusations of cowardice and self-interest, the colonels were forced to reinterpret their sense of duty and manliness, thereby emphasising civic responsibility in place of battlefield service.